(untitled) (Journal of Scientific Research, 2025)
Vibrational and electronic analyses were conducted for quinoxaline utilizing FT-IR, FT – Raman, and UV–Vis–NIR techniques. Infrared intensities, Raman scattering data, vibrational wavenumbers, molecular geometry, and optimal structure were determined using the Density Functional Theory/ Becke’s three-parameter exchange functional with the Lee-Yang-Parr correlation functional (DFT/B3LYP) method with a 6–31G** basis set. Electron localization and delocalization were examined through highest occupied molecular orbital and lowest unoccupied molecular orbital (HOMO–LUMO) analysis, while Molecular Electrostatic Potential (MEP) analyses were undertaken to identify potential electrophilic, nucleophilic, and radical attacks. The electron affinity, electronegativity, chemical potential, ionization potential, electrophilicity and hardness, softness, stability of the compound were characterized via FMO (Frontier Molecular Orbital) studies. Nonlinear optical (NLO) characterizations involved the determination of dipole moment, polarizability, and first–order hyperpolarizability. Additionally, Molecular Docking analysis of quinoxaline was carried out to know its binding orientation, affinity, and activity.